Critérios ESG e a responsabilidade jurídica das empresas transnacionais - Hudler, Daniel Jacomelli (2024)
The activities of transnational corporations (TNCs) have come under increasing scrutiny due to their potential environmental, social and human rights impacts. This study explores the emerging concept of ESG criteria and its implications for the legal responsibility of TNCs. The research objectives are threefold: (i) to define and characterize transnational business activities and TNCs; (ii) to delineate the concept of ESG criteria and its legal implementation modalities; (iii) to examine potential grounds for attributing legal responsibility to TNCs based on ESG criteria. The study employs a deductive approach, drawing upon multidisciplinary bibliographic research in the fields of Social Sciences, Sociology, Political Science, Anthropology, History, Accounting, and Business Administration. This research line is inherent to the theme of Business and Human Rights, which is part of the concentration area "Business Law: Structures and Regulation". The objective of this area is to study Business Law within "Research Line 2: Transnational Companies and Regulation", developed within the scope of the Doctoral Program at Nove de Julho University (PPGD-UNINOVE). Key findings: (i) TNCs aim to maximize production, facilitate the flow of goods and services, reduce transaction costs, achieve balance in relationships, comply with established rules, and generate profits. They wield significant influence regardless of nationality, corporate structure, or institutional interests, with notable political implications; (ii) ESG criteria can encompass a reporting framework with varied rules and metrics, considering the dynamic concept of materiality. Legal implementation modalities include voluntary adoption by companies subject to specific procedures (e.g., periodic reporting or submission for rating agency evaluation) or inclusion of specific contractual clauses; (iii) At this stage of development, addressing the issue through Transnational Law and Transnational Private Regulation is challenging due to the risk of marginalizing the State and the internationally recognized human rights system. Attributing legal responsibility to TNCs based on ESG criteria remains possible, even in the absence of a specific treaty, including on Human Rights and Business. Defense can be sought under domestic law, specifically Civil Law, based on subsidiary principles prohibiting contradictory behavior and promoting justice in conjunction with economic efficiency.